Accelerating trypsin digestion: the immobilized enzyme reactor. (October 2014) - Regnier, Fred E; Kim, JinHee
Sample preparation has lagged far behind the evolution of instrumentation used in mass-linked protein analysis. Trypsin digestion, for example, still takes a day, as it did 50 years ago, while mass spectral analyses are achieved in seconds. Higher order structure of proteins is frequently modified by varying digestion conditions: shifting the initial points of trypsin cleavage, changing digestion pathways, accelerating peptide bond demasking and altering the distribution of miscleaved products at the completion of proteolysis. Reduction and alkylation are even circumvented in many cases. This review focuses on immobilized enzyme reactor technology as a means to achieve accelerated trypsin digestion by exploiting these phenomena.